Cish knockout mice exhibit similar outcomes to malaria infection despite altered hematopoietic responses - Lakkavaram, Asha L.; Maymand, Saeed; Naser, Wasan; Ward, Alister C.; de Koning-Ward, Tania F. (Frontiers in Microbiology, 2023)
The Cytokine-inducible Src homology 2 domain-containing (CISH) protein is a negative feedback regulator induced by cytokines that play key roles in immunity and erythropoiesis.Single nucleotide polymorphisms (SNPs) in the human CISH gene have been associated with increased susceptibility to severe malaria disease. To directly assess how CISH might influence the outcomes of in the BALB/c model of an acute malaria infectionanemia, CISH knockout (Cish -/-) mice on this background were infected with Plasmodium berghei and their hematopoietic responses, cytokine production and ability to succumb to severe malaria disease evaluated. Despite basal erythrocytic disruption, upon P. berghei infection, the Cish -/-mice were better able to maintain peripheral blood cell counts, haemoglobin levels and a steadystate pattern of erythroid differentiation compared to wild-type (Cish +/+ ) mice. Ablation of CISH, however, did not influence the outcome of acute malaria infections in either the BALB/c model or the alternative C57BL/6 model of experimental cerebral malariamice, with the kinetics of infection, parasite load, weight loss and cytokine responses being similar between Cish +/+ and Cish -/-mice, while and both genotypes succumbed to experimental cerebral malaria within a comparable timeframe.